IJMA' ABOUT PRAYER WEARING MASK DURING THE COVID-19 PANDEMIC - Khalis Kohari (Fakultas Agama Islam Universitas Islam As Syafi'iyah, 2021)
This simple article aims to get to know more deeply about the ijma' prayer wearing a mask during the Covid-19 pandemic, covering the mouth is called talatsub, scholars agree that the law is forbidden by the Prophet so it is makruh to pray using a mask to cover your mouth is makruh but don't forget something that was previously makruh can turn into permissible when there is a need there is a need in the term ushul fiqh